2004
DOI: 10.1055/s-2004-837258
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Management of Brachial Plexus Birth Injuries: The Miami Experience

Abstract: This article reviews the authors' experience over the last decade in the multidisciplinary management of children with brachial plexus birth injuries. When compared with the results of a study of 91 children who received nonoperative treatment, the results of surgical intervention can improve the functional outcome in properly selected infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…Following the description of Kawabata and colleagues [9] of the use of the spinal accessory nerve as an ipsilateral nerve transfer to the suprascapular nerve in infants with upper brachial plexus birth injuries, its use has continued to expand. Total the scores for active abduction/forward flexion and active external rotation; from [7] a Maximum shoulder score=10; decrease score by 1 point for a contracture >20°T Several groups [1,6,8,11,14,19,20] have published variable experiences with the use of the distal SAN-to-SSN transfer as part of a primary or secondary plexus reconstruction in infants who fail to demonstrate spontaneous recovery of active shoulder external rotation following a period of observation. In a retrospective review of 86 infants, Pondaag et al [14] found similar clinical results and functional scores in infants undergoing C5-to-SSN bypass grafting (n=65) and those who received direct SANto-SSN (n=21) transfers performed at a mean of 5 months of age.…”
Section: Discussionmentioning
confidence: 99%
“…Following the description of Kawabata and colleagues [9] of the use of the spinal accessory nerve as an ipsilateral nerve transfer to the suprascapular nerve in infants with upper brachial plexus birth injuries, its use has continued to expand. Total the scores for active abduction/forward flexion and active external rotation; from [7] a Maximum shoulder score=10; decrease score by 1 point for a contracture >20°T Several groups [1,6,8,11,14,19,20] have published variable experiences with the use of the distal SAN-to-SSN transfer as part of a primary or secondary plexus reconstruction in infants who fail to demonstrate spontaneous recovery of active shoulder external rotation following a period of observation. In a retrospective review of 86 infants, Pondaag et al [14] found similar clinical results and functional scores in infants undergoing C5-to-SSN bypass grafting (n=65) and those who received direct SANto-SSN (n=21) transfers performed at a mean of 5 months of age.…”
Section: Discussionmentioning
confidence: 99%
“…4 All individuals were diagnosed at birth with an upper brachial plexus injury and referred for management to our multidisciplinary programme. The majority of infants referred for evaluation are surgical candidates for either early or late procedures.…”
Section: Methodsmentioning
confidence: 99%
“…4,6 Shoulder range of motion, including total shoulder elevation and active external rotation, were measured. Zero degrees of external rotation was the position of the arm when abducted at 90 degrees, with the elbow flexed to 90 degrees and the forearm and hand pronated and pointing forward.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations